Answer: ![4y^{2}(2x-9y)^{2}](https://tex.z-dn.net/?f=4y%5E%7B2%7D%282x-9y%29%5E%7B2%7D)
Step-by-step explanation:
We have the following polynomial:
![(4xy-18y^{2})^{2}](https://tex.z-dn.net/?f=%284xy-18y%5E%7B2%7D%29%5E%7B2%7D)
This is a polynomial of the form
. Following this rule to expand it, we have:
![(4xy)^{2}-2(4xy)(18y^{2})+(18y^{2})^{2}](https://tex.z-dn.net/?f=%284xy%29%5E%7B2%7D-2%284xy%29%2818y%5E%7B2%7D%29%2B%2818y%5E%7B2%7D%29%5E%7B2%7D)
![16x^{2}y^{2}-144xy^{3}+324y^{4}](https://tex.z-dn.net/?f=16x%5E%7B2%7Dy%5E%7B2%7D-144xy%5E%7B3%7D%2B324y%5E%7B4%7D)
Applying common factor
:
![4y^{2}(4x^{2}-36xy+81y^{2})](https://tex.z-dn.net/?f=4y%5E%7B2%7D%284x%5E%7B2%7D-36xy%2B81y%5E%7B2%7D%29)
Note the polynomial inside the parenthesis is a perfect square trinomial, which can be factored to
. Hence, the final simplification is:
![4y^{2}(2x-9y)^{2}](https://tex.z-dn.net/?f=4y%5E%7B2%7D%282x-9y%29%5E%7B2%7D)
You can factor a parabola by finding its roots: if
![p(x)=x^2+bx+c](https://tex.z-dn.net/?f=%20p%28x%29%3Dx%5E2%2Bbx%2Bc%20)
has roots
, then you have the following factorization:
![p(x) = (x-x_1)(x-x_2)](https://tex.z-dn.net/?f=%20p%28x%29%20%3D%20%28x-x_1%29%28x-x_2%29%20)
In order to find the roots, you can use the usual formula
![x_{1,2} = \dfrac{-b\pm\sqrt{b^2-4ac}}{2a}](https://tex.z-dn.net/?f=%20x_%7B1%2C2%7D%20%3D%20%5Cdfrac%7B-b%5Cpm%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%20)
In the first example, this formula leads to
![x_{1,2} = \dfrac{-2\pm\sqrt{4+4}}{2} = \dfrac{-2\pm\sqrt{8}}{2} = \dfrac{-2\pm2\sqrt{2}}{2} = 1 \pm \sqrt{2}](https://tex.z-dn.net/?f=%20x_%7B1%2C2%7D%20%3D%20%5Cdfrac%7B-2%5Cpm%5Csqrt%7B4%2B4%7D%7D%7B2%7D%20%3D%20%5Cdfrac%7B-2%5Cpm%5Csqrt%7B8%7D%7D%7B2%7D%20%3D%20%5Cdfrac%7B-2%5Cpm2%5Csqrt%7B2%7D%7D%7B2%7D%20%3D%201%20%5Cpm%20%5Csqrt%7B2%7D%20)
So, you can factor
![x^2-2x-1 = (x-1-\sqrt{2})(x-1+\sqrt{2})](https://tex.z-dn.net/?f=%20x%5E2-2x-1%20%3D%20%28x-1-%5Csqrt%7B2%7D%29%28x-1%2B%5Csqrt%7B2%7D%29%20)
The same goes for the second parabola.
As for the third exercise, simply plug the values asking
![f(1.5)=-5.25](https://tex.z-dn.net/?f=%20f%281.5%29%3D-5.25%20)
you get
![f(-1.5) = 1.5c-3 = -5.25](https://tex.z-dn.net/?f=%20f%28-1.5%29%20%3D%201.5c-3%20%3D%20-5.25%20)
Add 3 to both sides:
![1.5c = -2.25](https://tex.z-dn.net/?f=%201.5c%20%3D%20-2.25%20)
Divide both sides by 1.5:
![c = 1.5](https://tex.z-dn.net/?f=%20c%20%3D%201.5%20)
So if you want to fit the y-intercepts or "b", on the y-axis you should go by 25's [0, 25, 50, 75, 100...]
If the x-axis <u>does not have to</u> follow the same pattern (25's), you should go by 5's [0, 5, 10, 15, 20...]
y = 7x + 50
y = 2x + 175
First I would plot the y-intercepts for each equation, then plot a few points with x = 5, 10, 15 Then draw a straight line.
The point where the two lines meet/cross paths is your solution. It should be (25, 225) The x-axis is the number of miles, and the y-axis is the total cost. So Truck driver A and B would arrive/be at the same place/meet in 25 miles at the same cost of $225
Answer:
1 : 140
Step-by-step explanation:
Ratio is 30 : 4200
Divide both numbers by 30:-
= 1 : 140 (answer)
To answer the question above, use conversion factors and dimensional analysis. In this given, it is easier to use grams as the basis.
a. (2 centrigrams) x (1 gram / 100 centigrams) = 0.02 grams
b. 2 grams
c. (2 hectograms) x (1 gram / 0.01 hectogram) = 200 grams
d. (2 kilograms) x (1 gram / 0.001 kilogram) = 2000 grams
e. (2 milligrams) x (1 gram / 1000 millimeters) = 0.002 grams
Thus, the answer is 2 milligrams.